Indira Gandhi a/p Mutho v Pengarah Jabatan Agama Islam Perak & Ors and other appeals [2018] 1 MLJ 545: From Conflict of Jurisdictions to Reaffirmation of Constitutional Supremacy - Wei Jiet, Lim; Au Tian Hui, Abraham (Journal of Malaysian and Comparative Law, 2019)
It is hoped that the decision of Indira Gandhi, decided in the most fashionable manner that constitutional enthusiasts could expect, would finally put an end to the impasse in relation to the conflict in jurisdictions between the Civil and Syariah Courts. It is now for the executive and legislative branches of government to act on the judiciary’s clarion call and finally table the proposed amendments to section 88 of the LRA to be passed in Parliament70 as follows: (1) Where a party to a marriage has converted to Islam, the religion of any child of the marriage shall remain as the religion of the parties to the marriage prior to the conversion, except where both parties to the marriage agree to a conversion of the child to Islam, subject always to the wishes of the child where he or she has attained the age of eighteen years. (2) Where the parties to the marriage professed different religions prior to the conversion of one spouse to Islam, a child of the marriage shall be at liberty to remain in the religion of either one of the prior religions of the parties before the conversion to Islam.